2018
DOI: 10.1186/s12885-018-4304-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq reveals the existence of a CDKN1C-E2F1-TP53 axis that is altered in human T-cell lymphoblastic lymphomas

Abstract: BackgroundPrecursor T-cell lymphoblastic lymphomas (T-LBL) are rare aggressive hematological malignancies that mainly develop in children. As in other cancers, the loss of cell cycle control plays a prominent role in the pathogenesis in these malignancies that is primarily attributed to loss of CDKN2A (encoding protein p16INK4A). However, the impact of the deregulation of other genes such as CDKN1C, E2F1, and TP53 remains to be clarified. Interestingly, experiments in mouse models have proven that conditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…3c and Supplementary File 3) where E2F transcription factor 1 (E2F1) was the hub gene because E2F1 mediates TP53-dependent apoptosis. This pathway is critical for the current study because of the TP53 −/− driver mutation described earlier [23].…”
Section: Wgcna Discriminates Metastasismentioning
confidence: 99%
“…3c and Supplementary File 3) where E2F transcription factor 1 (E2F1) was the hub gene because E2F1 mediates TP53-dependent apoptosis. This pathway is critical for the current study because of the TP53 −/− driver mutation described earlier [23].…”
Section: Wgcna Discriminates Metastasismentioning
confidence: 99%
“… 48 For CDKN1C, its loss could be attributable to hyperactivation of p53 at the DN3–DN4 transition. 49 , 50 Also, it was reported that in quercetin- and cisplatin-treated cells, the expression of CDKN1C, CCNA2, CCND2 ,CCND3, CCNE1, and CDK2 could be simultaneously elevated. 51 Thus, we suspected there might be some interactions between STEAP3 and CDKN1C, and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, besides epigenetic changes and signal-transduction modulation, regulation by microRNAs might be an additional mechanism contributing to p57 level control in a wide variety of solid and liquid tumors [ 141 ]. Particularly, miR25, miR221, and miR222 were reported as able to directly target CDKN1C RNA in gastric cancer [ 142 ], hepatocellular carcinoma (HCC), and human T-cell lymphoblastic lymphomas [ 143 ], and miR-92b has been reported as responsible for p57 downregulation in HCC tissues and cell lines, enhancing tumor radio-resistance to ionization radiation (IR)-based radiotherapy [ 144 ].…”
Section: P27 and P57 Proteins’ Major Features Properties And Funmentioning
confidence: 99%